If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 = m Solving -2 = m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. -2 + -1m = m + -1m Combine like terms: m + -1m = 0 -2 + -1m = 0 Add '2' to each side of the equation. -2 + 2 + -1m = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1m = 0 + 2 -1m = 0 + 2 Combine like terms: 0 + 2 = 2 -1m = 2 Divide each side by '-1'. m = -2 Simplifying m = -2
| 14xy(xy)=0 | | (a-4)(a^2-2a+1)= | | 5x=y+1 | | 5N+3=-12 | | 4n-2n+8=3n-1 | | 11-x=-6 | | 24=m+3 | | 0.4*5+2x-0.5=3*0.3+0.7 | | (6+5)(-3a+8)=136 | | 2(x-1)(x-1)-9(x-1)-5=0 | | 2x^8-6x^7+10x^6= | | (p-1)(p+10)= | | 0.1h+2=3 | | 9_-2m+2-3= | | -85+12x=59 | | 2x+3-(x-2)=4+(x+3) | | 9x+10=21x | | 2x^7-6x^7+10x^6= | | 7C-8=6 | | .25x+13=.5x+31.75 | | 12x-12x-20=1 | | 6+5(3a+8)=136 | | 9n+12=39 | | 4(2x+y)+7y= | | -p-4p-10= | | 3(5)+y=18 | | 3-5k+2k=-6 | | 3w=-15+5w | | B-49=-45 | | -10y+18=-3*5y-7+5y | | 4y+3=-5 | | 20t-19t=10 |